Implementasi Pemberian Edukasi Kesehatan dan Kebugaran Remaja Putri dalam Menurunkan Gejala Dysmenorhae Primer di SMP Al-Hidayah - Sri Handayani; Rasumawati Rasumawati; Endah Dian Marlina (PPNI UNIMMAN, 2024)
Premenstrual syndrome is a set of physical, emotional, and behavioral symptoms that occur cyclically before menstruation, typically 1-14 days prior and disappear once menstruation begins. The COVID-19 pandemic can exacerbate this situation by increasing academic and social stress levels among adolescent girls. Through counseling and practical sessions, adolescents are provided with an understanding of the importance of reproductive health and physical skills to manage dysmenorrhea symptoms. This community service aims to reduce primary dysmenorrhea symptoms in adolescent girls at Al-Hidayah Middle School, South Jakarta, through the implementation of health and fitness education. The methods used include providing Health and Fitness Education with pre-tests and post-tests to measure their understanding of dysmenorrhea; teaching adolescents how to reduce menstrual pain through videos, guided by educators and accompanied by assistants; and conducting evaluations to ensure understanding and enhance their interest. The results showed an increase in knowledge and a reduction in PMS anxiety among the adolescent girls. In conclusion, this activity successfully improved adolescents' understanding of reproductive health, but further evaluation is needed to measure its long-term impact.